2019
DOI: 10.1016/s0140-6736(19)30773-1
|View full text |Cite|
|
Sign up to set email alerts
|

Prophylactic antibiotics in the prevention of infection after operative vaginal delivery (ANODE): a multicentre randomised controlled trial

Abstract: Summary Background Risk factors for maternal infection are clearly recognised, including caesarean section and operative vaginal birth. Antibiotic prophylaxis at caesarean section is widely recommended because there is clear systematic review evidence that it reduces incidence of maternal infection. Current WHO guidelines do not recommend routine antibiotic prophylaxis for women undergoing operative vaginal birth because of insufficient evidence of effectiveness. We aimed to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 21 publications
0
58
0
2
Order By: Relevance
“…The ANODE trial was a multicentre, randomised, blinded, controlled trial done at 27 hospital obstetric units in the UK. 133 Women who had undergone birth by forceps or vacuum at 36 weeks or greater gestation, with no indication for ongoing prescription of antibiotics in the postpartum period and no contraindications to prophylactic amoxicillin and clavulanic acid, were randomly assigned (1:1) to receive a single intravenous dose of prophylactic amoxicillin and clavulanic acid or placebo. The proportion of women who had overall primary outcome events was higher than anticipated (486 [15%] of 3225).…”
Section: Evidence Level 1++mentioning
confidence: 99%
“…The ANODE trial was a multicentre, randomised, blinded, controlled trial done at 27 hospital obstetric units in the UK. 133 Women who had undergone birth by forceps or vacuum at 36 weeks or greater gestation, with no indication for ongoing prescription of antibiotics in the postpartum period and no contraindications to prophylactic amoxicillin and clavulanic acid, were randomly assigned (1:1) to receive a single intravenous dose of prophylactic amoxicillin and clavulanic acid or placebo. The proportion of women who had overall primary outcome events was higher than anticipated (486 [15%] of 3225).…”
Section: Evidence Level 1++mentioning
confidence: 99%
“…We advocated the use of short-term prophylactic antibiotics after repair of complex perineal tears but not simple tears. A recently published large multicentre randomized trial found that one prophylactic dose of antibiotic in women undergoing operative vaginal birth significantly reduced the rate of perineal infection [29].…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are no international guidelines that recommend routine antibiotic prophylaxis for women undergoing OVD as there is insufficient evidence to support the effectiveness of this practice. A recent trial was published from the UK, which investigated the role of antibiotic prophylaxis in preventing maternal infection after OVD . The authors carried out a blinded, randomized controlled trial which took place at 27 obstetric units in the UK.…”
Section: Should We Give Prophylactic Antibiotics Routinely After Opermentioning
confidence: 99%